Co-Simulation Model for Determination of Optimal Active Power Filters Settings in Low-Voltage Network - Mario Primorac; Zvonimir Klaić; Heidi Adrić; Matej Žnidarec (Applied Sciences)
Current trends in the use of energy storage, electric mobility, and the integration of a large number of distributed generations at the distribution level can have positive effects on reducing loads and losses in the network. An excessive and uncontrolled level of integration of the above trends leads to various problems related to the power quality. Distortion of the voltage and current waveforms caused by nonlinear loads is manifested through harmonics and can be classified as one of the most essential parameters of electricity quality. Reducing harmonics thus becomes the primary goal for improving the quality of electricity at the distribution level. This paper, along with a detailed analysis of the literature, provides an overview of different views on the problems of optimal allocation of active filters and emphasizes the importance that the problem of optimal allocation of active filters should be based on the variability of the harmonic spectrum as a function of time. Installing devices for reducing harmonics in the network, in terms of improving the quality of electricity, is one of the essential elements from both a technical and an economic point of view and can solve these challenges. Therefore, it is necessary to develop methods for solving the problem of determining the position, size and parameters of filters, as well as the number of buses on which such devices can be integrated. Applying optimization techniques enables the development of more realistic models for applying active power filters. The research in this paper is directed toward developing a co-simulation optimization model to determine optimal settings of the parallel APF due to harmonic reduction in a real low-voltage network using particle swarm optimization for 24 h intervals. The research in this paper was conducted on a real radial low-voltage feeder, where at each node, the variability of production and/or consumption is taken, which is obtained on the basis of real measurements and tests. Based on this, the position and dimensioning of the shunt active power filters (APFs) depend on the load range within a 24 h interval at all nodes in the observed time interval. Furthermore, the paper emphasizes the importance of observing Voltage Total Harmonic Distortion (THDV) on the busbars in the depth of the feeder as well as the importance of observing THDV in each phase.